UPAYA MENINGKATKAN MOTORIK HALUS MELALUI KIRIGAMI UNTUK ANAK USIA DINI 5-6 TAHUN DI TK IQRO ISLAMIC PRESCHOOL BEKASI - Ela Tri Laelasari (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2021)
This study aims to determine the improvement of students' fine motor skills using kirigami in early childhood 5-6 years at Iqro Islamic Preschool Kindergarten Bekasi. This research is a collaborative classroom action research (CAR) carried out in two cycles. The subjects of this study were children aged 5-6 years. Data collection techniques using observation sheets. The data analysis used is descriptive qualitative. Improvement of fine motor skills is said to be successful if the percentage of children's fine motor skills reaches > 65%. Based on the percentage analysis of the results of this study, the results of pre-action observations of students' fine motor skills were 43.79%. After taking action in the first cycle, the percentage increase was 68.4%. After doing the action in the second cycle, the students' average fine skills increased to 73.9%. Thus the results of the analysis state that kirigami can improve fine motor skills in early childhood.